1993
DOI: 10.1210/mend.7.3.8387158
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 3 beta-hydroxysteroid dehydrogenase and 17 beta-hydroxysteroid dehydrogenase messenger ribonucleic acid levels by cyclic adenosine 3',5'-monophosphate and phorbol myristate acetate in human choriocarcinoma cells.

Abstract: 3 beta-Hydroxysteroid dehydrogenase (3 beta HSD) in human placenta converts 3 beta-hydroxy-5-ene steroids producing progesterone, whereas 17 beta-hydroxysteroid dehydrogenase (17 beta HSD) mediates the interconversion of estrone and estradiol. We first showed that the expression of type I 17 beta HSD (17 beta HSD-I) gene was undetectable in human JEG-3 cells. We then studied the effects of cAMP- and protein kinase-C-dependent pathways on the expression of 3 beta HSD-I and 17 beta HSD-II genes using an analog o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 0 publications
0
23
3
Order By: Relevance
“…It is more likely that the observed effects are due to the interaction with receptor or cell signalling rather than cytotoxic responses. Moreover, gene transcription of 3␤-HSD1 has been reported to be affected by cellular adenosine 3 ,5 -cyclic monophosphate (cAMP) via a protein kinase (PK) A-dependent mechanism [20] and by cellular calcium content via a PKC-dependent pathway [29]. Perturbation of calcium homeostasis [30] and induction of cAMP level [31] by OTA may contribute to the modulation of 3␤-HSD1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is more likely that the observed effects are due to the interaction with receptor or cell signalling rather than cytotoxic responses. Moreover, gene transcription of 3␤-HSD1 has been reported to be affected by cellular adenosine 3 ,5 -cyclic monophosphate (cAMP) via a protein kinase (PK) A-dependent mechanism [20] and by cellular calcium content via a PKC-dependent pathway [29]. Perturbation of calcium homeostasis [30] and induction of cAMP level [31] by OTA may contribute to the modulation of 3␤-HSD1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the two isoforms of human 3␤-HSD are regulated by different transcription factors [for a review, see 28], previous studies have demonstrated that similar signal transduction pathways such as cAMP-related protein kinase A and phorbol ester/phorbol myristate acetate-related PKC pathways are involved in the regulation of human 3␤-HSD gene expression [20,32,33]. OTA may possibly induce similar effects in other steroidogenic organs/tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA from guinea pig tissues and adrenal cells were isolated by homogenization in 4 M guanidinium thiocyanate, centrifuged through a 5.7 M CsCl cushion (Chirgwin et al, 1979), and fractionated by electrophoresis as described (Tremblay et al, 1989;Tremblay and Beaudoin, 1993).…”
Section: Mrna Preparation and Analysismentioning
confidence: 99%
“…A rat 18S ribosomal RNA oligodeoxyribonucleotide probe (Clements et al, 1988), synthesized (Bioresearch DNA synthesizer), and end-labeled with [-/-"PJATP, was used to assess the amount and integrity of RNA loaded (Tremblay and Beaudoin, 1993).…”
Section: Mrna Preparation and Analysismentioning
confidence: 99%